Geoinformática aplicada na estimativa do potencial fotovoltaico do semiárido sergipano - Feitosa, Rodrigus Oliveira (2022)
The development of society has always demanded a growing need for energy, and in modern times environmental concern adds to this demand the use of cleaner and renewable sources. Brazil has great availability of renewable resources, mainly the sun. Studies have shown that Brazilian solar energy potential, especially on semi-arid region, exceeds the average potential of the whole Europe. To analyze the solar potential in a region, it is necessary to apply expensive technologies that, due to extension of semi-arid region, would be financially unfeasible. However, some methodologies applied on remote sensing products can significantly reduce this problem. We hypothesized that it would be possible to apply geoinformatics resources to estimate the potential for solar energy generation on semi-arid region of Sergipe, and thus produce useful data and information to analyze the environmental, energy and socioeconomic impacts on the poorest region of Brazil. Thus, we defined as a general objective, to analyze the potential of photovoltaic (PV) electric energy generation on semi-arid region of Sergipe using geoinformatics resources. Thus, we performed the determination of parameters for modeling solar radiation by a GIS; we developed an algorithm in computational language to automate the modeling; we model solar radiation; we analyze the ideal locations for installing photovoltaic plants; we calculate the electricity generation potential of photovoltaic plants; and, finally, we evaluated the impacts of the entry of the solar source of electric energy in the semi-arid region of Sergipe. The applied methodology mainly used high resolution satellite images and the r.sun solar analysis module of the GRASS SIG. The analysis of ideal locations was based on a process hierarchical analysis method and weighted overlap analysis. Results show that the potential of semi-arid region of Sergipe is superior to data obtained in another study carried out at national level and this could have a great impact on local population. We observed that the use of remote sensing products with better resolution and a study on regional or local level produces much more accurate results, as well as use of historical data is of paramount importance to analyze the temporal variations of solar radiation and changes in the terrain. The average PV potential calculated is between 5.16 and 5.78 kWh/m2/day, and the energy impact for Sergipe would be very significant. The environmental impact is considerable as long as PV energy generated is sufficient to prevent activation of thermoelectric plants. And social impact would only exist significantly with implementation of a productive chain of PV energy.